Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1189/jlb.0805488
|View full text |Cite
|
Sign up to set email alerts
|

Roles of leukocytosis and cysteinyl leukotriene in polymorphonuclear leukocyte-dependent plasma extravasation

Abstract: The PMN-dependent plasma extravasation is a major mechanism of permeability enhancement in acute inflammation. To reveal the pathophysiological significance of the PMN-dependent plasma extravasation, we prepared a systemic leukocytotic guinea pig model by a daily injection of recombinant human (rh)G-CSF. The extent of the PMN-dependent plasma extravasation, regarded as the late-phase permeability induced by an intradermal injection of zymosan-activated guinea pig plasma (ZAP) or of rhC5a, clearly correlated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Arachidonic acid can also be converted to cysteinyl leukotrienes (LTs) by the action of 5-LOX. The cysteinyl LTs are potent mediators of allergy and inflammation by modulation of the smooth muscle tone and vascular permeability (Kanaoka et al, 2006;Tokita et al, 2006). In addition, they play an important role in asthma and other respiratory diseases (Lewis et al, 1990;McMillan et al, 1992;Henderson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Arachidonic acid can also be converted to cysteinyl leukotrienes (LTs) by the action of 5-LOX. The cysteinyl LTs are potent mediators of allergy and inflammation by modulation of the smooth muscle tone and vascular permeability (Kanaoka et al, 2006;Tokita et al, 2006). In addition, they play an important role in asthma and other respiratory diseases (Lewis et al, 1990;McMillan et al, 1992;Henderson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For the latter function, we examined granule release induction and respiratory burst induction in neutrophils and vascular permeability enhancement in guinea pig skin. In the latter case, the histamine release reaction of cutaneous mast cells and the arachidonate cascade reaction of migrating neutrophils are involved [19,25]. Furthermore, we have revealed that the guinea pig C5a receptor recognizes human C5a [16] as well as E. coli Skp [1].…”
Section: Conversion Of Skp To Possess Chemoattractant/ Secretagogue Cmentioning
confidence: 83%
“…In contrast to the neutrophil number, the fluid volume did not increase. The neutrophil extravasation associates vascular permeability enhancement via cysteinyl leukotriene generation by the neutrophils and endothels in their corporation . The disassociation between the neutrophil number and the fluid volume suggests that the increased neutrophil number would be mainly due to retardation of the neutrophil clearance once infiltrated.…”
Section: Discussionmentioning
confidence: 99%